2022
DOI: 10.3390/cancers14030691
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplant for Hematologic and Oncologic Diseases: Principle and Practice

Abstract: Understanding of the importance of the normal intestinal microbial community in regulating microbial homeostasis, host metabolism, adaptive immune responses, and gut barrier functions has opened up the possibility of manipulating the microbial composition to modulate the activity of various intestinal and systemic diseases using fecal microbiota transplant (FMT). It is therefore not surprising that use of FMT, especially for treating relapsed/refractory Clostridioides difficile infections (CDI), has increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…In addition to restoring the balance of microbial community in the intestine, it provides a mean to replenish the microbial community with SCFA producers to fortify the intestinal barrier. FMT may be therapeutically beneficial to patients with various hematologic and oncologic diseases [123]. In addition to treating malignancy-associated recurrent/refractory C. diff.…”
Section: Fecal Microbiota Transplantmentioning
confidence: 99%
“…In addition to restoring the balance of microbial community in the intestine, it provides a mean to replenish the microbial community with SCFA producers to fortify the intestinal barrier. FMT may be therapeutically beneficial to patients with various hematologic and oncologic diseases [123]. In addition to treating malignancy-associated recurrent/refractory C. diff.…”
Section: Fecal Microbiota Transplantmentioning
confidence: 99%
“…With respect to other approaches (applying probiotics and prebiotic components), fecal microbiota transplantation is worked quicker and is more effective in the reconstitution of the intestinal microflora [ 172 ]. Moreover, FMT showed more success in controlling Clostridium difficile infection because feces contain additional metabolites such as proteins, bacteriophages, and bile acids [ 173 ].…”
Section: Manipulating the Microbiota For Cancer Therapymentioning
confidence: 99%
“…Faecal microbiota transplant (FMT) is an emerging therapeutic approach in many potential applications and has primarily been applied in patients with relapsed/refractory Clostridioides difficile infection. Due to the complexity of the diseases and their treatment, patients with haematologic and oncologic diseases are particularly susceptible to complications related to altered intestinal microbiota [ 28 ]. Currently, there are nearly 40 studies registered that primarily evaluate the safety of FMT, the use of FMT following allogeneic hematopoietic stem cell transplantation, improvement in ICI response, and the treatment of the complications that arise due to cancer therapy [ 28 ].…”
Section: Human Microbiota and The Relation With The Hostmentioning
confidence: 99%
“…Due to the complexity of the diseases and their treatment, patients with haematologic and oncologic diseases are particularly susceptible to complications related to altered intestinal microbiota [ 28 ]. Currently, there are nearly 40 studies registered that primarily evaluate the safety of FMT, the use of FMT following allogeneic hematopoietic stem cell transplantation, improvement in ICI response, and the treatment of the complications that arise due to cancer therapy [ 28 ]. Various retrospective studies suggested a possible relation between broad-spectrum antibiotics, altered intestinal microbiota and its negative impact on responses to ICI treatment in cancer patients [ 29 , 30 , 31 , 32 ].…”
Section: Human Microbiota and The Relation With The Hostmentioning
confidence: 99%